2012
DOI: 10.1371/journal.pone.0034070
|View full text |Cite
|
Sign up to set email alerts
|

Convergent, Parallel and Correlated Evolution of Trophic Morphologies in the Subfamily Schizothoracinae from the Qinghai-Tibetan Plateau

Abstract: Schizothoracine fishes distributed in the water system of the Qinghai-Tibetan plateau (QTP) and adjacent areas are characterized by being highly adaptive to the cold and hypoxic environment of the plateau, as well as by a high degree of diversity in trophic morphology due to resource polymorphisms. Although convergent and parallel evolution are prevalent in the organisms of the QTP, it remains unknown whether similar evolutionary patterns have occurred in the schizothoracine fishes. Here, we constructed for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
51
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 39 publications
4
51
0
1
Order By: Relevance
“…Despite being a harsh environment due to its high elevation, the Qinghai Tibetan Plateau (QTP) is known as a hot spot of biodiversity because of its high species richness and abundant endemic species (Myers et al, 2000;Qi et al, 2012). The Schizothoracinae, also called "snow trout", is a subfamily of the Cyprinidae, and comprises 10-13 genera with about 100 species (Mizra, 1991).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Despite being a harsh environment due to its high elevation, the Qinghai Tibetan Plateau (QTP) is known as a hot spot of biodiversity because of its high species richness and abundant endemic species (Myers et al, 2000;Qi et al, 2012). The Schizothoracinae, also called "snow trout", is a subfamily of the Cyprinidae, and comprises 10-13 genera with about 100 species (Mizra, 1991).…”
mentioning
confidence: 99%
“…The specialized group consists of Ptychobarbus, Gymnodiptychus and Diptychus, and is characterized by the absence of uroneuralia, one or two rows of pharyngeal teeth, and significant but moderate degeneration of the scales. The highly specialized group consists of Gymnocypris, Oxygymnocypris, Schizophygopsis, Chuanchia and Platypharodon, and is characterized by a total absence of barbels and scales, and a well-developed canalis preoperculomandibularis (Qi et al, 2012). Molecular phylogenetic studies identified two distinct clades in the schizothoracine fish: the first clade comprises the primitive group, and the second clade the specialized and highly specialized groups (He et al, 2004;Qi et al, 2012).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…黄河裸裂尻鱼(Schizopygopsis pylzovi)隶属鲤形 目 (Cypriniformes) 鲤 科 (Cyprinidae) 裂 腹 鱼 亚 科 (Schizothoracinae), 广泛分布于青藏高原东北部兰 州以上黄河干支流、湖泊、沼泽、柴达木水系以及 湟水河水系中 (Wu & Wu, 1991)。栖息于水质清澈、 水流缓慢、水底多砾石的水域, 通常以浮游动植物 或底栖动植物为食料, 在青藏高原淡水生态系统的 食物链中具有重要的地位。同其他裂腹鱼亚科鱼类 一样, 黄河裸裂尻鱼具有生长期短、生长缓慢、 性成熟迟以及繁殖力低等典型生物学特性, 加之 受人类活动和环境恶化的影响, 近年来黄河裸裂尻 鱼 种 群 数 量 锐 减 , 栖 息 水 域 明 显 萎 缩 (Qi et al, 2007)。 目前对黄河裸裂尻鱼的研究主要集中在形态 分类、生物学特性、遗传多样性、系统发育和人 工繁殖等方面 (Wu, 1984;Wu & Wu, 1991;Qi et al, 2007Qi et al, , 2008Qi et al, , 2009Qi et al, , 2012 …”
unclassified